Prevalence and determinants of nutritional status among women and children in Pakistan - Hanumant Waghmare; Shekhar Chauhan; Santosh Kumar Sharma (BMC, 2022)
Abstract Background Nutrition has been a low-priority area in Pakistan, with low visibility from the political leadership. Despite various efforts, Pakistan has been reported to have one of the highest prevalences of child and women malnutrition compared to other developing counties. Therefore, this study intends to examine the prevalence and determinants of nutritional status of women and children in Pakistan. Methods The present study uses the Demographic Health Survey (DHS) data from Pakistan 2012-13 (PDHS-3). The nutritional status of women was examined through Body-Mass Index (Underweight, normal, overweight, & obese), and that of children was examined through stunting (severe and moderate), wasting (severe, moderate, overweight), and underweight (severe, moderate, overweight). Descriptive statistics and bivariate analysis have been used along with multinomial logistic regression. Results A higher proportion of children in rural areas were severely stunted (19.6% vs. 12.5%), severe wasted (2.4% vs. 2.2%), and severe underweight (9.4% vs. 6%) than their urban counterparts. A higher proportion of rural women (9.5% vs. 5.5%) were underweight than urban women, whereas a higher proportion of urban women were obese (24.3% vs. 19.0%) than rural women. The odds of severe stunting (OR = 0.24; C.I. = 0.15-0.37), severe underweight (OR = 0.11; C.I. = 0.05-0.22) were lower among children from the richest wealth quintile than their poorest counterparts. The Relative Risk Ratio (RRR) of being overweight (RRR = 3.7; C.I. = 2.47-5.54) and Obese (RRR = 4.35; C.I. = 2.67-7.07) than normal BMI were higher among women from richest wealth quintile than women belonged to poorest wealth quintile. Conclusion This study has highlighted determinants associated with maternal and child nutritional status, whereby the child's nutritional status was measured by stunting, wasting, and underweight, and BMI measured the mother's nutritional status. The main risk factors for a child's poor nutritional status include low household wealth, urban residence, and mother's educational status. Similarly, the main risk factors for women's poor nutritional status include increasing the women's age, educational status, rural residence, and household wealth. Poor households should be provided special attention to improve the nutritional status among women and children in poor households.